2016
DOI: 10.1002/cam4.871
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for IGF‐1 in the development of second primary cancers?

Abstract: Cancer survival rates are increasing, and as a result, more cancer survivors are exposed to the risk of developing a second primary cancer (SPC). It has been hypothesized that one of the underlying mechanisms for this risk could be mediated by variations in insulin‐like growth factor‐1 (IGF‐1). This review summarizes the current epidemiological evidence to identify whether IGF‐1 plays a role in the development of SPCs. IGF‐1 is known to promote cancer development by inhibiting apoptosis and stimulating cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 129 publications
2
41
0
2
Order By: Relevance
“…[ 18 20 ] Furthermore, the use of quantitative PCR, permits a highly sensitive quantification of IGF-1 expression, to investigate the correlation between this gene expression in the serum of breast cancer patients and susceptibility to tumor recurrence; however, there are controversies in the studies involving clinical features of breast cancer and the expression levels of IGF-1. [ 21 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 20 ] Furthermore, the use of quantitative PCR, permits a highly sensitive quantification of IGF-1 expression, to investigate the correlation between this gene expression in the serum of breast cancer patients and susceptibility to tumor recurrence; however, there are controversies in the studies involving clinical features of breast cancer and the expression levels of IGF-1. [ 21 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence derived from systematic meta-analyses that raised serum IGF-1 levels are associated with increased risk of PCa [ 153 157 ]. At present, epidemiologists focus on the role of milk-induced IGF-1 signaling in PCa and have demonstrated a relationship between milk consumption, increased serum IGF-1 levels and increased risk of PCa [ 130 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since many of these outcomes have also been associated with alterations in circulating insulin-like growth factor-1 (IGF-1), several studies have suggested a possible interaction between vitamin D and IGF-1 [4,5,6]. IGF-1 possesses key roles in regulating cellular proliferation and apoptosis as well as energy metabolism, body size, and organ-specific functions [7,8].…”
Section: Introductionmentioning
confidence: 99%